2016
DOI: 10.1021/acssuschemeng.6b00711
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Containing Ionic Liquids as Synergistic Catalysts for the Cycloaddition of CO2: A Density Functional Theory and Response Surface Methodology Corroborated Study

Abstract: Metal-containing ionic liquids possessing bifunctional moieties were identified as efficient catalysts for the synthesis of propylene carbonate (PC) from CO 2 and propylene oxide under moderate and solvent free conditions. Density functional theory calculations were performed to rationalize the difference in catalytic activities of the metalcontaining ionic liquid catalysts (MeIm) 2 MCl 2 , where M was Fe, Cu, or Zn. (MeIm) 2 ZnCl 2 was the most efficient catalyst for the chemical fixation of carbon dioxide in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 61 publications
1
32
0
Order By: Relevance
“…If combined with suitable organicc ations, these units are the basis for a large group of MILs, the halidometallate ILs, which arguablyi s the largest subgroup of MILs studied today. [10,11,[27][28][29][30][31][32][33][34][35][36] However,a lthough many different metals are in principle amenablet ot he synthesis of halidometallateI Ls, there are still only few reports on MILs containing more than one metal. Very recently,L iu et al [37] demonstrated mixed metal ILs by combining monometallic ILs with an additional metal salt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If combined with suitable organicc ations, these units are the basis for a large group of MILs, the halidometallate ILs, which arguablyi s the largest subgroup of MILs studied today. [10,11,[27][28][29][30][31][32][33][34][35][36] However,a lthough many different metals are in principle amenablet ot he synthesis of halidometallateI Ls, there are still only few reports on MILs containing more than one metal. Very recently,L iu et al [37] demonstrated mixed metal ILs by combining monometallic ILs with an additional metal salt.…”
Section: Introductionmentioning
confidence: 99%
“…; X=Cl, Br, I) unit. If combined with suitable organic cations, these units are the basis for a large group of MILs, the halidometallate ILs, which arguably is the largest subgroup of MILs studied today [10, 11, 27–36] …”
Section: Introductionmentioning
confidence: 99%
“…It is not only time‐consuming, but also unlikely to reflect the interactions among the parameters. Response surface methodology (RSM) is a very useful technique for the prediction of the most efficient sets of conditions with minimum number of tests . It also provides statistical models for assessing the influence of the parameters on the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The BMMs−Zn&ILs‐1.7 shows the highest yield of 98% with the selectivity of 97%. It was explained that the cooperation catalysis between Zn and ILs promoted the ring addition reaction, and the Zn acted as an assistant catalyst when it was used together with ILs for the synthesis of CO 2 with PO to PC [7d] . Moreover, It is well known that halide anions have a significant effect on the catalytic reactivity, which is strongly depend on the order of halide ion nucleophilicity (Cl − <Br − <I − ).…”
Section: Resultsmentioning
confidence: 99%
“…So far, zinc salts have been proven to be the best candidate, because of its high activity and low toxicity [7d,8a] . For example, the activity of catalysts could be increased about 15.5 or 27 times by adding ZnBr 2 compare to bare 1‐butyl‐3‐methylimidazolium chloride ([C 4 ‐mim]Cl) or tetrabutylammonium iodide respectively [8] .…”
Section: Introductionmentioning
confidence: 99%